THE RELATIONSHIP BETWEEN CLOCK DRAWING AND COGNITION IN PARKINSON'S. Issue 11 (14th October 2015) - Cosgrove, Jeremy; Jamieson, Stuart; Smith, Stephen; Alty, Jane
Abstract : Introduction: Clock drawing (CD) requires executive function, attention and visuospatial ability. Our objective was to investigate CD in Parkinson's subjects with and without cognitive impairment. Methods: 107 subjects completed the Montreal Cognitive Assessment (MoCA), classifying into normal cognition (PD-NC – MoCA ≥26) and cognitive impairment (PD-CI–MoCA <26). CD was scored using MoCA criteria; a maximum of 3 points, one each for correct contour, clock face and clock hands. Results: PD-CI (n=57) and PD-NC were matched for all demographics except age (PD-CI were older, P 0.032). 35% of PD-CI scored full marks compared to 90% of PD-NC (sensitivity 0.64, specificity 0.9, age adjusted-odds ratio for predicting PD-CI 15.63, 95% CI 5.18 – 47.62, P<0.001). 88% of PD-CI scored points for contour and 60% scored points for clock face. In contrast, all PD-NC scored points for contour and clock face (P <0.001). 42% of PD-CI and 90% of PD-NC correctly drew clock hands (P<0.001). Conclusions: In this cohort, inability to score maximum points for CD was associated with PD-CI. Correctly drawing clock hands was the hardest component for both groups. Incorrect contour or clock face was highly specific for PD-CI.